The Influence of Trust, Security and Convenience on Consumer Satisfaction of J&T Express, Bima Regency - Nurlinda Linda; Muhajirin Muhajirin (Universitas Muhammadiyah Makassar, 2024)
The purpose of the study is to determine and analyze the effect of trust, security and convenience on customer satisfaction for J&T Express, Bima Regency. This research is an associative research using quantitative data from primary data sources. The research instrument used a Likert scale questionnaire. The research population is all consumers who use J&T Express services in Bima Regency whose exact number is unknown (Unknown Population), so that a sample of 96 respondents uses a purposive sampling technique. Data collection techniques using observation, literature study questionnaires. Data analysis techniques using validity test, reliability test, classic assumption test, multiple linear regression analysis, multiple correlation coefficients, determination test, t test and f test. The results of the study stated that trust, security and convenience had an effect on consumer satisfaction for J&T Express, Bima Regency.